2021
DOI: 10.3389/fnint.2021.792863
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Activity During Hypoxia Improves Functional Outcomes in Motor Neuron Networks in vitro

Abstract: The effects of hypoxia, or reduced oxygen supply, to brain tissue can be disastrous, leading to extensive loss of function. Deoxygenated tissue becomes unable to maintain healthy metabolism, which leads to increased production of reactive oxygen species (ROS) and loss of calcium homoeostasis, with damaging downstream effects. Neurons are a highly energy demanding cell type, and as such they are highly sensitive to reductions in oxygenation and some types of neurons such as motor neurons are even more susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As shown in Figure 2 , our engineered neural networks expressed both the excitatory neuronal marker CaMKIIa, and the inhibitory neuronal marker GAD65/67 in conjunction with the neuronal marker MAP2 by 21 DIV, strongly indicating the capacity for excitatory – inhibitory synaptic transmission within the maturing networks. This was further verified through recordings of electrophysiological activity, which showed that in healthy conditions, networks developed highly dynamic and complex age-dependent firing activity and network bursts over time, in line with previous studies by us and others (Chiappalone et al, 2006; Chiappalone et al, 2007; Fiskum et al, 2021; van de Wijdeven et al, 2018; Weir et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…As shown in Figure 2 , our engineered neural networks expressed both the excitatory neuronal marker CaMKIIa, and the inhibitory neuronal marker GAD65/67 in conjunction with the neuronal marker MAP2 by 21 DIV, strongly indicating the capacity for excitatory – inhibitory synaptic transmission within the maturing networks. This was further verified through recordings of electrophysiological activity, which showed that in healthy conditions, networks developed highly dynamic and complex age-dependent firing activity and network bursts over time, in line with previous studies by us and others (Chiappalone et al, 2006; Chiappalone et al, 2007; Fiskum et al, 2021; van de Wijdeven et al, 2018; Weir et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…The timing of media change relative to the time of recording is also likely to affect network activity. For example, human motor neurons were found to have a higher firing frequency 24 hours after media change compared to 48 hours after media change (Fiskum et al, 2021). The fact that we recorded activity 72 hours after media change may thus contribute to the very low burst propensity exhibited in our networks.…”
Section: Discussionmentioning
confidence: 99%
“…A signal was defined and recorded as a spike when reaching beyond a differential threshold of 7.5 times the standard deviation of the background activity. Firing rate and burst propensity (a measure of fraction of spikes in networks bursts) were analysed using an in-house made MATLAB script, reported previously (Fiskum et al, 2021). A network burst was identified when a binned spike distribution of 50ms bins exceeded a threshold of firing rate of 7.5 standard deviations and more than 20% of all active electrodes in the recording fired.…”
Section: Methodsmentioning
confidence: 99%
“…For further information see S3 Table It should also be noted that the rate of membrane depolarization increases as the available oxygen concentration at the neuron decreases. This behaviour was reported in both brain slices and in vitro cultures exposed to hypoxia [64,[67][68][69][70], and can be explained by the fact that a reduced availability of oxygen causes a break in the homeostatic maintenance of ion concentrations between inner and outer neuron environments, which is responsible for sustaining the electrical activity of the neuron. Essentially, when oxygen levels are reduced, the Na + -K + -ATP pump lacks resources for fuelling ion transport.…”
Section: Discussionmentioning
confidence: 77%